Diagnosis and management of tumor lysis syndrome. Issue 3 (3rd May 2020) - Puri, Isha; Sharma, Deep; Gunturu, Krishna S.; Ahmed, Andaleeb A.
ABSTRACT: Tumor lysis syndrome (TLS) is an oncological emergency characterized by a classic tetrad of hyperuricemia, hyperkalemia, hyperphosphatemia, and hypocalcemia. Risk assessment and prophylactic therapy is critical in preventing this oncological emergency. Treatment of established TLS involves aggressive hydration, electrolyte management, and the use of hypouricemic agents.